Milton : Modern Judgementsd - Bren, Milton H.; Alperson, Edward L., 1896-1969; Lieberson, Goddard, 1911-1977.; Brenco Pictures Corporation; Warner Brothers Collection (Library of Congress); Copyright Collection (Library of Congress) (United States : Warner Bros. Pictures, 1968)
Romantic complications ensue when a famous screen star and her small adopted daughter, traveling without Pullman reservations, usurp the compartment of a handsome but shy biochemistry professor.
Copyright: Brenco Pictures Corp. 12Jun52; LP1760.
Summary taken from PREMARC card.
Based on the novel of the same title by Goddard Lieberson.
Sources used: PREMARC card, LCCN Fi 52-002103; Copyright catalog, motion pictures, 1950-1959; Internet movie database 10/29/04.
Associate producer, Edward L. Alperson, Jr. ; music, Heinz Roemheld ; film editor, Arthur Hilton ; cinematography by Ernest Laszlo.
Gloria Swanson, James Warren, Fred Clark, Hans Conreid, Steve Brodie.
Keywords: Comedy films; Feature films